Antineutrophil Cytoplasmic Antibodies Associated With Infective Endocarditis. Issue 3 (January 2016) - Langlois, Vincent; Lesourd, Anais; Girszyn, Nicolas; Ménard, Jean-Francois; Levesque, Hervé; Caron, Francois; Marie, Isabelle
Abstract : Abstract: To determine the prevalence of antineutrophil cytoplasmic antibodies (ANCA) in patients with infective endocarditis (IE) in internal medicine; and to compare clinical and biochemical features and outcome between patients exhibiting IE with and without ANCA. Fifty consecutive patients with IE underwent ANCA testing. The medical records of these patients were reviewed. Of the 50 patients with IE, 12 exhibited ANCA (24%). ANCA-positive patients with IE exhibited: longer duration between the onset of first symptoms and IE diagnosis ( P  = 0.02); and more frequently: weight loss ( P  = 0.017) and renal impairment ( P  = 0.08), lower levels of C-reactive protein ( P  = 0.0009) and serum albumin ( P  = 0.0032), involvement of both aortic and mitral valves ( P  = 0.009), and longer hospital stay ( P  = 0.016). Under multivariate analysis, significant factors for ANCA-associated IE were: longer hospital stay ( P  = 0.004), lower level of serum albumin ( P  = 0.02), and multiple valve involvement ( P  = 0.04). Mortality rate was 25% in ANCA patients; death was because of IE complications in all these patients. Our study identifies a high prevalence of ANCA in unselected patients with IE in internal medicine (24%). Our findings further underscore that ANCA may be associated with a subacute form of IE leading to multiple valve involvement and more frequent renal impairment. Because death was due to IE complications in all patients, our data suggest that aggressive therapy may be required to improve such patients' outcome.